Revisiting Canale and Swain’s Communicative Competence: Contextual Arabic Language Learning in the Merdeka Curriculum Era - Mursyidan, Maftukh Ghulam; Thohir, Muhammad; Nuzula, Anisah Firdausi; Tuada, Linura (al-Ittijah: Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2025)
This study explores the use of Canale and Swain’s communicative competence framework in teaching Arabic through contextual activities in the Merdeka Curriculum. The issue is relevant because schools are expected to help students communicate more naturally, not only master grammar. The research aimed to see how teaching practices encourage the development of grammatical, discourse, sociolinguistic, and strategic abilities. A qualitative descriptive approach was applied by gathering information through interviews, classroom observations, and a review of teaching documents. The data were examined through a gradual process of sorting, organizing, and interpreting. The results show that contextual tasks and project-based work give students more room to improve their grammatical and discourse skills, which also supports their confidence and fluency. In contrast, sociolinguistic and strategic skills have not grown as strongly, mainly because authentic materials are scarce, lesson time is limited, and teachers need more support in designing communicative activities. The study underscores the continued relevance of communicative competence in Arabic learning and points to the importance of providing richer learning media, performance-based assessments, and sustainable teacher development. Future studies may look into digital and authentic resources to strengthen all components of communicative competence.